The Ethics of Educational Healthcare Placements in Low and Middle Income Countries First Do No Harm? - Ahmed, Anya; Ackers-Johnson, James; Ackers, Helen Louise (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
XI, 158 p. 12 illus., 11 illus. in color.